Blue School Project: Project Based Learning Berbasis Pesisir untuk menanamkan kepedulian Lingkungan Siswa MI - Moh. Mundzir (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
Coastal environments play a strategic role in the sustainability of ecosystems and social life, but face various problems due to low environmental awareness. Early environmental education, especially in Madrasah Ibtidaiyah (MI) in coastal areas, is an important effort in shaping students' ecological character. This study aims to analyze the implementation of the Blue School Project as a coastal-based Project-Based Learning (PjBL) model, supporting and inhibiting factors, and initial impacts on student awareness and participation. The study uses a descriptive qualitative approach at MI Manbaul Ma'arif Kingking Tuban through observation, interviews, and documentation. The results show that the Blue School Project is implemented in accordance with PjBL principles and has a positive impact on gradually increasing students' environmental awareness.